The Application of Black Phosphorus Nanomaterials in Bone Tissue Engineering - Xirui Jing; Zekang Xiong; Zian Lin; Tingfang Sun (MDPI AG, 2022)
Recently, research on and the application of nanomaterials such as graphene, carbon nanotubes, and metal-organic frameworks has become increasingly popular in tissue engineering. In 2014, a two-dimensional sheet of black phosphorus (BP) was isolated from massive BP crystals. Since then, BP has attracted significant attention as an emerging nanomaterial. BP possesses many advantages such as light responsiveness, electrical conductivity, degradability, and good biocompatibility. Thus, it has broad prospects in biomedical applications. Moreover, BP is composed of phosphorus, which is a key bone tissue component with good biocompatibility and osteogenic repair ability. Thereby, BP exhibits excellent advantages for application in bone tissue engineering. In this review, the structure and the physical and chemical properties of BP are described. In addition, the current applications of BP in bone tissue engineering are reviewed to aid the future research and application of BP.